FINANCIAL CRISIS VERSUS DEBATE ON URBAN SPACE, CHALLENGE, AND RESEARCH AGENDA - Sutriadi, Ridwan (Journal of Indonesian Economy and Business, 2010)
Unstable economic conditions due to the financial crisis in 1997 and 2008 have madeÂ it necessary for Indonesia to seek alternative ways to escape such uncertain globalÂ economic conditions. In doing so, several development policies and innovative scenariosÂ have been applied by the Indonesian Republic. The government has also attempted toÂ relate such initiatives with global development actors, starting from the policy level upÂ until the formulation of action plans. Nevertheless these efforts must be accompanied by aÂ comprehensive approach, covering all activity aspects from the actors of development toÂ collectively participate in development. This may also effect development of IndonesianÂ urban space of which cannot be separated from such global conditions.This article attempts to describe the impacts of development beyond the limits ofÂ administration as a result of globalization, occurring particularly in large cities, but alsoÂ involving other cities Indonesia. In relation to this, the discourse on âspaceâ emerges in theÂ context of urban planning, whether remaining to be oriented towards physicalorganization, or shifted to the new paradigm of which tends to view space as a product ofÂ global economic situations, community conditions, as well as values of local culture andforeign values (imported from the west). Therefore, this article begins its discussion onÂ urban systems within the context of globalization and financial crisis, then proceeding withÂ discussions concerning impacts towards urban structure, regional competition, urbanÂ identity, followed by discussions on financial crisis and the debate on urban space, andÂ finally concluded with the research agenda.Paradigm shifts have become one of the most urgent matters to study considering theÂ challenges of inter-regional competition, regional autonomy, and financial crisis.Furthermore, this study may assist the space planners in better understanding the reasonsÂ that cause failures of policy and planning implementation that have been formulated. ThisÂ article aims to awaken academicians in developing a research agenda in line with theÂ debates of understanding urban space (particularly in times of financial crisis) but alsoÂ serves as a critic and enrichment towards the literature related to global impacts towardsÂ urban structure, regional competition, and urban identity.Keywords: globalization, space, urban structure, regional competitiveness, urban identity.